Molecular modeling of some mono-and disaccharides - Mainal, Azizah; Hashim, Rauzah; Mahmood, Kamaliah (Malaysian Journal of Science, 2001)
The Î± and Î²-forms of different saccharides are randomly selected to calculate their minimum energies using molecular mechanics (MM) methodology. The cff91-force field is used to optimize the sugars, employing the Newton-Raphson minimization method. ln addition, the AMPAC/MOPAC program is used to calculate the electronic energies of the optimized sugars. The calculated results are discussed within the aspect of anomeric and solvation effects. In the cyclic versus open-chain glucose discussion, the theoretical results are compared with the spectral (NMR and IR) results of glucose. To conclude our study, a preliminary work on the united atom force field calculation is carried out by estimating the volume of the sugar heads represented as spherical and ellipsoidal models.The Î± and Î²-forms of different saccharides are randomly selected to calculate their minimum energies using molecular mechanics (MM) methodology. The cff91-force field is used to optimize the sugars, employing the Newton-Raphson minimization method. ln addition, the AMPAC/MOPAC program is used to calculate the electronic energies of the optimized sugars. The calculated results are discussed within the aspect of anomeric and solvation effects. In the cyclic versus open-chain glucose discussion, the theoretical results are compared with the spectral (NMR and IR) results of glucose. To conclude our study, a preliminary work on the united atom force field calculation is carried out by estimating the volume of the sugar heads represented as spherical and ellipsoidal models.The Î± and Î²-forms of different saccharides are randomly selected to calculate their minimum energies using molecular mechanics (MM) methodology. The cff91-force field is used to optimize the sugars, employing the Newton-Raphson minimization method. ln addition, the AMPAC/MOPAC program is used to calculate the electronic energies of the optimized sugars. The calculated results are discussed within the aspect of anomeric and solvation effects. In the cyclic versus open-chain glucose discussion, the theoretical results are compared with the spectral (NMR and IR) results of glucose. To conclude our study, a preliminary work on the united atom force field calculation is carried out by estimating the volume of the sugar heads represented as spherical and ellipsoidal models.The Î± and Î²-forms of different saccharides are randomly selected to calculate their minimum energies using molecular mechanics (MM) methodology. The cff91-force field is used to optimize the sugars, employing the Newton-Raphson minimization method. ln addition, the AMPAC/MOPAC program is used to calculate the electronic energies of the optimized sugars. The calculated results are discussed within the aspect of anomeric and solvation effects. In the cyclic versus open-chain glucose discussion, the theoretical results are compared with the spectral (NMR and IR) results of glucose. To conclude our study, a preliminary work on the united atom force field calculation is carried out by estimating the volume of the sugar heads represented as spherical and ellipsoidal models.The Î± and Î²-forms of different saccharides are randomly selected to calculate their minimum energies using molecular mechanics (MM) methodology. The cff91-force field is used to optimize the sugars, employing the Newton-Raphson minimization method. ln addition, the AMPAC/MOPAC program is used to calculate the electronic energies of the optimized sugars. The calculated results are discussed within the aspect of anomeric and solvation effects. In the cyclic versus open-chain glucose discussion, the theoretical results are compared with the spectral (NMR and IR) results of glucose. To conclude our study, a preliminary work on the united atom force field calculation is carried out by estimating the volume of the sugar heads represented as spherical and ellipsoidal models.The Î± and Î²-forms of different saccharides are randomly selected to calculate their minimum energies using molecular mechanics (MM) methodology. The cff91-force field is used to optimize the sugars, employing the Newton-Raphson minimization method. ln addition, the AMPAC/MOPAC program is used to calculate the electronic energies of the optimized sugars. The calculated results are discussed within the aspect of anomeric and solvation effects. In the cyclic versus open-chain glucose discussion, the theoretical results are compared with the spectral (NMR and IR) results of glucose. To conclude our study, a preliminary work on the united atom force field calculation is carried out by estimating the volume of the sugar heads represented as spherical and ellipsoidal models.